Implementasi Perda Qanun di Aceh terhadap Anak Dibawah Umur yang Melakukan Perjudian - Permatasari, Dewi Cahyani Nigita; Nugrono, Bastianto; Supolo, Supolo (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2022)
Law Number 11 of 2007 concerning the Government of Aceh is the legal order in the legal system and national legislation system. In Article 1 number 21 of Law Number 11 of 2006, it is determined that "Aceh Qanun is a statutory regulation similar to a provincial regional regulation that regulates the administration of government and the life of the Acehnese people". Article 233 paragraph (1) stipulates that "qanuns are established in the context of administering the Aceh Government, district/city administrations and implementing co-administration tasks". However, some matters regarding the content of the qanun are different from the general “regional regulations”, which are based on the LoGA. One thing that is very specific about the content of the qanun is the provisions contained in the provisions of Article 241 paragraph 4 of the PA Law. In Article 143 paragraph (2) of Law no. 32 Year 2004. This study examines how the implementation of criminal justice for children as perpetrators of gambling crimes according to the Aceh Qanuns which are fundamentally related to the legal policies and objectives that underlie the regulation of juvenile criminal justice in Indonesia, such as in the paradigm of child protection, child development, retributive, and retorative. This type of research is normative juridical (legal research), using a statute approach, conceptual approach, and case approach.